ANALISIS PENENTUAN PERSEDIAAN BAHAN BAKU KEDELAI YANG OPTIMAL DENGAN MENGGUNAKAN METODE STOCKHASTIC PADA PT. LOMBOK GANDARIA - Yusniaji, Fahmi -; Widajanti, Erni - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT The purpose of this study was to determine the efficiency of determining the need for raw material supplies by PT. Lombok Gandaria Solo, so as to maintain the stability of production. Research methods using case studies in PT. Lombok Gandaria Solo, data collection methods used : interviews, observation, and documentation. Data analysis techniques used in this study is a stochastic inventory control models. Results of calculation of the total inventory cost of raw materials showed that the inventory cost the company more than the total cost of inventory is calculated according to the method stochastic, so if PT. Lombok Solo Gandaria using stochastic inventory control methods will obtain cost savings. So that the hypothesis " that the alleged supply of raw material requirements determination made by PT. Lombok Gandaria Solo in maintaining the stability of inefficient production" unsubstantiated. Keywords : stochastic inventory control models, raw material supplies